2017
DOI: 10.1016/j.jaci.2016.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Allergen endotoxins induce T-cell–dependent and non–IgE-mediated nasal hypersensitivity in mice

Abstract: Antigen-specific nasal activation of CD4 T cells followed by endotoxin exposure induces mast cell/basophil-independent histamine release in the nose that elicits sneezing responses. Thus, environmental or nasal residential bacteria may exacerbate AR symptoms. In addition, this novel phenomenon might explain currently unknown mechanisms in allergic(-like) disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…On the other hand, conditional pathogens (such as Enterobacteriaceae), which can produce harmful metabolites such as lipopolysaccharide, are increased. Lipopolysaccharide can promote the differentiation of Th2 cells ( Iwasaki et al., 2017 ), which can further promote the production of IgE by B cells, leading to the activation of mast cells to participate in the pathogenesis of CSD ultimately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, conditional pathogens (such as Enterobacteriaceae), which can produce harmful metabolites such as lipopolysaccharide, are increased. Lipopolysaccharide can promote the differentiation of Th2 cells ( Iwasaki et al., 2017 ), which can further promote the production of IgE by B cells, leading to the activation of mast cells to participate in the pathogenesis of CSD ultimately.…”
Section: Resultsmentioning
confidence: 99%
“…Both Enterobacteriaceae and Klebsiella are Gram-negative bacteria, which can produce lipopolysaccharide. Existing studies have shown that lipopolysaccharide can induce nasal hypersensitivity in mice by activating Th2 cells ( Iwasaki et al., 2017 ). These results imply that opportunistic pathogens may also play a role in the pathogenesis of CSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, exposure to >2,000 EU LPS/m 3 can cause severe toxic pneumonia 18 , 19 ) . A key component of LPS-mediated inflammation is an enhanced T-helper-type 2 cell (T H 2) reactivity 20 , 21 , 22 ) . Swine farm workers exhibit an immune dysregulation characterized by preferential activation of a T H 2 response 23 ) .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of ovalbumin (OVA) sensitization, it is not clear whether endotoxin is required to trigger the optimal response. In a series of elegant experiments, 75 it was shown that endotoxin-containing but not endotoxin-free OVA elicited sneezing responses in mice independent of IgE. Local activation of antigen-specific T H 2 cells was required for this response, and this was dependent on TLR4 signaling.…”
Section: Cd4 T Cells and T-cell Subsetsmentioning
confidence: 99%